Difabel dalam Kitab Tafsir Indonesia Kontemporer - Rikho Afriyandi; Fadli Rahman (Syams, 2020)
This article explores contemporary (20th century) commentaries in Indonesia to see the views of these commentators on diffables in their interpretation. Until now, people with disabilities are still underestimated. Even long before that, namely from before entering the 20th century, people with disabilities have experienced various discrimination. Various terms of language elements that have the meaning of insulting, degrading, etc. have been widely used, such as people with disabilities, idiots, disorders, blindness, and so on. Protection for persons with disabilities in Indonesia only appeared in 1997 in the form of a law. At the same time, many interpretations were born at that time, namely from the beginning of the 20th century until the emergence of the Law. This paper concludes that: First, diffables are people who have physical or mental disorders that can interfere or constitute an obstacle and obstacle for them to carry out normal activities but still be able to carry out their activities in a different way. Second, Al-Qur’an does not explain diffable explicitly. However, there are several terms he uses regarding diffables, namely summun, bukmun, 'umyun and a'raj, which mean deaf, mute, blind and lame. Al-Qur’an, in its explanation, divides the diffable into two parts, namely physical disabilities and mental disabilities. Physical disabilities as referred to in Al-Qur’an are used to describe the limitations or imperfections that exist in a person or person. Meanwhile, mental diffable is used to refer to people who are blind, deaf, and mute theologically. Third, all Mufassirs who lived during the 20th century, in general really care about the existence of people with disabilities.